Method for manufacturing printed wiring board
The method of forming cavities in printed wiring boards by sandblasting a cured layer from a thermosetting resin composition containing white inorganic pigments addresses the challenge of light scattering, achieving improved processability and reflectivity.
Patent Information
- Application Number
- JP2020152865
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-09-11
AI Technical Summary
The formation of cavities in printed wiring boards with reflective sheets containing white inorganic pigments is challenging due to light scattering, leading to distorted cavity shapes and reduced processability.
A manufacturing method involving the preparation of a cured layer from a thermosetting resin composition containing a white inorganic pigment, followed by sandblasting to form a cavity, which improves processability and achieves high reflectivity.
The method enables the formation of cavities with high accuracy and intended shape, enhancing the workability and reflectivity of the printed wiring boards.
Smart Images

Figure 0007647039000002 
Figure 0007647039000003 
Figure 0007647039000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a printed wiring board. [Background technology]
[0002] Light-emitting diodes (LEDs), which emit light with low power, are increasingly being mounted directly on printed wiring boards for use as backlights for liquid crystal displays in mobile terminals, computers, televisions, etc., and as light sources for lighting fixtures.
[0003] A reflective sheet for reflecting light may be formed on the outermost layer of such a printed wiring board in order to increase the efficiency of extracting light emitted from a light source (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6078595 Summary of the Invention [Problem to be solved by the invention]
[0005] The reflective sheet of the printed wiring board for LED display is often formed by a photosensitive resin composition containing a white inorganic pigment. When forming a cavity in the reflective sheet formed by the photosensitive resin composition, photolithography has been generally used in the past. Specifically, it has been generally used to form a latent image on the reflective sheet by exposing it through a photomask, and then develop the latent image to form a cavity having a desired pattern shape.
[0006] However, during exposure, the light is scattered by the white inorganic pigment, so that exposure may occur in unintended parts of the reflective sheet. For example, light scattered by the white inorganic pigment may enter a part of the reflective sheet covered by a photomask, resulting in exposure of a part that should not be exposed. When such a phenomenon occurs, the shape of the resulting cavity is likely to be distorted, making it more difficult to form a cavity having the intended shape. Therefore, there is a demand for the development of a technology that improves processability in the process of forming a cavity in a cured layer using a resin composition containing a white inorganic pigment that can achieve high reflectance.
[0007] The present invention has been made in view of the above problems, and an object of the present invention is to provide a method for manufacturing a printed wiring board which has excellent processability when forming a cavity in a cured layer having a high reflectance. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above-mentioned problems, and as a result, have found that a manufacturing method including the steps of preparing a cured layer formed of a cured product of a thermosetting resin composition containing an inorganic filler including a white inorganic pigment, and subjecting the cured layer to a sandblasting treatment to form a cavity can solve the above-mentioned problems, and have completed the present invention. That is, the present invention includes the following.
[0009] [1] A step of preparing a cured layer formed of a cured product of a thermosetting resin composition containing an inorganic filler including a white inorganic pigment; and a step of sandblasting the cured layer to form a cavity. [2] The method for producing a printed wiring board according to [1], wherein the reflectance of the cured product to light with a wavelength of 460 nm is 85% or more. [3] The aspect ratio of the cavity is 1.0 or less, The method for manufacturing a printed wiring board according to [1] or [2], wherein the inclination angle of the wall surface of the cavity is 60° or more. [4] The method for producing a printed wiring board according to any one of [1] to [3], wherein the cured layer has a thickness of 5 μm or more and 150 μm or less. [5] The amount of the inorganic filler is 20% by mass or more and 70% by mass or less based on 100% by mass of the non-volatile components of the resin composition; The method for producing a printed wiring board according to any one of [1] to [4], wherein the amount of the white inorganic pigment is 10% by mass or more and 60% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. [6] The method for producing a printed wiring board according to any one of [1] to [5], wherein the resin composition contains an epoxy resin. [7] The method for producing a printed wiring board according to any one of [1] to [6], wherein the step of preparing the cured layer includes the steps of preparing a layer of the resin composition and thermally curing the layer of the resin composition. [8] The method for manufacturing a printed wiring board according to any one of [1] to [7], wherein the step of forming the cavity includes the steps of placing a mask having an opening on the hardened layer, and spraying abrasive grains onto the hardened layer through the opening of the mask. [9] The method for producing a printed wiring board according to [8], wherein the average particle size of the abrasive grains is 0.5 μm or more and 50 μm or less.
[10] The method for producing a printed wiring board according to [8] or [9], wherein the abrasive grains have a modified Mohs hardness of 5 or more.
[11] The method for producing a printed wiring board according to any one of [1] to
[10] , wherein the cured layer is an interlayer insulating layer or a solder resist layer of the printed wiring board. Effect of the Invention
[0010] According to the present invention, it is possible to provide a method for producing a printed wiring board which is excellent in processability when forming a cavity in a cured layer having a high reflectance. [Brief description of the drawings]
[0011] [Figure 1]FIG. 1 is a cross-sectional view that illustrates a typical cured layer prepared in step (I) for explaining a method for producing a printed wiring board according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates a state in which a dry film is provided on a cured layer in step (II-1) to explain a method for producing a printed wiring board according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view that illustrates a typical state in which an exposure treatment is performed on a dry film in step (II-1) for illustrating a method for producing a printed wiring board according to one embodiment of the present invention. [Figure 4] FIG. 4 is a cross-sectional view that illustrates a schematic view of the dry film after development processing in step (II-1) for illustrating a method for producing a printed wiring board according to one embodiment of the present invention. [Diagram 5] FIG. 5 is a cross-sectional view that illustrates a schematic state after sandblasting in step (II-2) for illustrating a method for producing a printed wiring board according to one embodiment of the present invention. [Figure 6] FIG. 6 is a cross-sectional view that illustrates an example of a printed wiring board manufactured by a manufacturing method according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below with reference to preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.
[0013] [1. Overview of printed wiring board manufacturing methods] A method for manufacturing a printed wiring board according to an embodiment of the present invention includes a step (I) of preparing a cured layer formed of a cured product of a thermosetting resin composition containing an inorganic filler, and a step (II) of forming a cavity in the cured layer. The inorganic filler contained in the thermosetting resin composition contains a white inorganic pigment. In addition, the step (II) includes performing a sandblasting treatment on the cured layer to form the cavity.
[0014] In the method for producing a printed wiring board, the cured layer is formed by a cured product of a thermosetting resin composition containing a white inorganic pigment. Since the white inorganic pigment can effectively reflect light, the cured layer can have a high light reflectance. In addition, in the method for producing a printed wiring board, a cavity is formed in the cured layer by a sandblasting process. Since the sandblasting process can physically scrape the cured layer with abrasive grains to form a cavity, the influence of light reflection by the white inorganic pigment can be eliminated. In addition, since the sandblasting process does not generate a large amount of heat and does not require the use of a chemical solution that corrodes the cured layer, deterioration of the resin component can be suppressed. Therefore, since unintended deformation of the cavity due to light, heat, and chemical solutions can be suppressed, the processability during cavity formation is excellent. Therefore, it is possible to easily produce a cavity in the cured layer with high precision in the shape as intended, and therefore excellent processability can be achieved.
[0015] [2. Step (I) of preparing a hardened layer] In step (I), a cured layer formed of a cured product of a resin composition is prepared. The cured layer may be prepared by purchasing it from the market, or may be prepared by manufacturing it using a resin composition. When a cured layer is manufactured using a resin composition layer, step (I) may include a step (I-1) of preparing a layer of the resin composition, and a step (I-2) of thermally curing the layer of the resin composition to obtain a cured layer. Hereinafter, the layer of the resin composition may be appropriately referred to as a "resin composition layer".
[0016] [2.1. Thermosetting resin composition] <(A) Inorganic filler> The thermosetting resin composition includes an inorganic filler (A). The inorganic filler (A) includes a white inorganic pigment (A-1). In one embodiment, the white inorganic pigment (A) refers to an inorganic compound having a reflectance of 90% or more for light with a wavelength of 500 nm. The white inorganic pigment (A) does not include silica. The white inorganic pigment (A) generally has a function of improving reflectance. The white inorganic pigment (A) may be used alone or in combination of two or more kinds.
[0017] Examples of the (A-1) white inorganic pigment material include white metal oxides such as aluminum oxide (alumina), titanium oxide, zirconium oxide, magnesium oxide, zinc oxide, cerium oxide, antimony oxide, tin oxide, barium titanate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, barium titanate zirconate, barium zirconate, and calcium zirconate; white metal sulfides such as zinc sulfide and strontium sulfide; and aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and the like. white metal hydroxides; white metal nitrides such as boron nitride, aluminum nitride, manganese nitride, etc.; white metal carbonates such as calcium carbonate, barium carbonate, magnesium carbonate, strontium carbonate, lead carbonate, etc.; white metal sulfates such as barium sulfate, calcium sulfate, lead sulfate, etc.; white metal phosphates such as zinc phosphate, titanium phosphate, zirconium phosphate, zirconium tungstate phosphate, etc.; white metal borates such as aluminum borate, etc.; and white minerals such as cordierite, talc, clay, mica, hydrotalcite, boehmite, etc.
[0018] Among these, the (A-1) white inorganic pigment is preferably selected from aluminum oxide, titanium oxide, zirconium oxide, magnesium oxide, barium titanate, zinc oxide, cerium oxide, and calcium carbonate, and titanium oxide is particularly suitable. As the titanium oxide, any of rutile type, anatase type, and brookite type may be used, but from the viewpoint of further improving the reflectance, the rutile type is preferable. As the titanium oxide, those obtained by a method such as a sulfuric acid method or a chlorine method can be used. The material of the (A-1) white inorganic pigment may be one type alone or a mixture of two or more types. The shape of the (A-1) white inorganic pigment may be, for example, any of an irregular shape, a crushed shape, a scaly shape, and a spherical shape.
[0019] Examples of commercially available white inorganic pigments (A-1) include "PX3788" manufactured by Sakai Chemical Industry Co., Ltd.; Typec "CR-50", "CR-57", "CR-80", "CR-90", "CR-93", "CR-95", "CR-97", "CR-60", "CR-63", "CR-67", "CR-58", "CR-85", and "UT771" manufactured by Ishihara Sangyo Kaisha; Typepure "R-100", "R-101", "R-102", "R-103", "R-104", "R-105", "R-108", "R-900", "R-902", "R-960", "R-706", and "R-931" manufactured by DuPont; "AHP300" manufactured by Nippon Light Metal Co., Ltd.; and Alnabeads "CB-P05" and "CB-A30S" manufactured by Showa Denko KK.
[0020] The specific surface area of the white inorganic pigment (A-1) is preferably 0.5 m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 2m 2 / g or more. There is no particular upper limit, but it is preferably 80m 2 / g or less, 70m 2 / g or less or 60m 2 The specific surface area is determined by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountec Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.
[0021] From the viewpoint of significantly obtaining the desired effects of the present invention, the average particle size of the (A-1) white inorganic pigment is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and is preferably 5 μm or less, more preferably 2 μm or less, even more preferably 1 μm or less.
[0022] The average particle size of the (A-1) white inorganic pigment can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the (A-1) white inorganic pigment is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample can be prepared by weighing 100 mg of the (A-1) white inorganic pigment and 10 g of methyl ethyl ketone into a vial and dispersing the mixture by ultrasonic waves for 10 minutes. The measurement sample can be measured by using a laser diffraction particle size distribution measuring device with blue and red light source wavelengths and a flow cell method to measure the volume-based particle size distribution of the (A-1) white inorganic pigment, and the average particle size can be calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.
[0023] From the viewpoint of improving moisture resistance and dispersibility, the (A-1) white inorganic pigment is preferably treated with a surface treatment agent. The surface treatment agent may be used alone or in any combination of two or more. Examples of the surface treatment agent include silane coupling agents such as vinyl silane coupling agents, epoxy silane coupling agents, styryl silane coupling agents, (meth)acrylic silane coupling agents, amino silane coupling agents, isocyanurate silane coupling agents, ureido silane coupling agents, mercapto silane coupling agents, isocyanate silane coupling agents, acid anhydride silane coupling agents, alkyl silane coupling agents, and phenyl silane coupling agents. From the viewpoint of improving reflectance, the surface treatment agent is preferably a silane coupling agent that does not contain a nitrogen atom, and is particularly preferably a silane coupling agent selected from phenyl silane coupling agents, alkyl silane coupling agents, epoxy silane coupling agents, vinyl silane coupling agents, (meth)acrylic silane coupling agents, and styryl silane coupling agents.
[0024] Examples of phenyl silane coupling agents include phenyl trimethoxy silane and phenyl triethoxy silane. Examples of alkyl silane coupling agents include methyl trimethoxy silane, dimethyl dimethoxy silane, methyl triethoxy silane, dimethyl diethoxy silane, n-propyl trimethoxy silane, n-propyl triethoxy silane, hexyl trimethoxy silane, hexyl triethoxy silane, octyl triethoxy silane, decyl trimethoxy silane, and 1,6-bis (trimethoxy silyl) hexane. Examples of epoxy silane coupling agents include 2- (3,4-epoxy cyclohexyl) ethyl trimethoxy silane, 3-glycidoxy propyl methyl dimethoxy silane, 3-glycidoxy propyl trimethoxy silane, 3-glycidoxy propyl methyl diethoxy silane, and 3-glycidoxy propyl triethoxy silane.
[0025] Examples of vinyl-based silane coupling agents include vinyltrimethoxysilane and vinyltriethoxysilane. Examples of (meth)acrylic-based silane coupling agents include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane. Examples of styryl-based silane coupling agents include p-styryltrimethoxysilane.
[0026] Commercially available surface treatment agents include, for example, "KBM-103" and "KBE-103" (phenyl silane coupling agents) manufactured by Shin-Etsu Chemical Co., Ltd.; "KBM-13", "KBM-22", "KBE-13", "KBE-22", "KBM-3033", "KBE-3033", "KBM-3063", "KBE-3063", "KBE-3083", "KBM-3103C", "KBM-3066", and "KBM-7103" (alkyl silane coupling agents); -1003", "KBE-1003" (vinyl silane coupling agent); "KBM-303", "KBM-402", "KBM-403", "KBE-402", "KBE-403" (epoxy silane coupling agent); "KBM-1403" (styryl silane coupling agent); "KBM-502", "KBM-503", "KBE-502", "KBE-503", "KBM-5103" ((meth)acrylic silane coupling agent).
[0027] The degree of surface treatment with the surface treatment agent is preferably within a predetermined range from the viewpoint of improving the dispersibility of the (A-1) white inorganic pigment. Specifically, 100 parts by mass of the (A-1) white inorganic pigment is preferably surface-treated with 0.2 to 5 parts by mass of the surface treatment agent, more preferably with 0.2 to 3 parts by mass, and even more preferably with 0.3 to 2 parts by mass.
[0028] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of the (A-1) white inorganic pigment. From the viewpoint of improving the dispersibility of the (A-1) white inorganic pigment, the amount of carbon per unit surface area of the (A-1) white inorganic pigment is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of suppressing an increase in the melt viscosity of the resin varnish and the melt viscosity in the form of a sheet, it is more preferable that the content is 1 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:
[0029] The carbon amount per unit surface area of the (A-1) white inorganic pigment can be measured after the surface-treated (A-1) white inorganic pigment is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the (A-1) white inorganic pigment that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the carbon amount per unit surface area of the (A-1) white inorganic pigment can be measured using a carbon analyzer. The carbon analyzer that can be used is, for example, the "EMIA-320V" manufactured by Horiba, Ltd.
[0030] From the viewpoint of effectively increasing the reflectance of the cured product and effectively increasing the processability during cavity formation, the amount of the white inorganic pigment (A-1) contained in the resin composition is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and is preferably 60% by mass or less, more preferably 55% by mass or less, even more preferably 50% by mass or less, and particularly preferably 40% by mass or less, based on 100% by mass of non-volatile components in the resin composition.
[0031] The (A) inorganic filler may further contain (A-2) an optional inorganic filler in combination with the (A-1) white inorganic pigment, if necessary. The (A-2) optional inorganic filler does not include the (A-1) white inorganic pigment. As the (A-2) optional inorganic filler, for example, an inorganic filler having a reflectance of less than 90% for light with a wavelength of 500 nm may be used.
[0032] Among them, from the viewpoint of effectively increasing the reflectance of the cured product and effectively increasing the processability during cavity formation, silica is preferred as the optional inorganic filler (A-2). Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. Moreover, as the silica, spherical silica is preferred.
[0033] Examples of commercially available silica products include "UFP-30" manufactured by Denka; "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", and "YA010C" manufactured by Admatechs; "Silfill NSS-3N", "Silfill NSS-4N", and "Silfill NSS-5N" manufactured by Tokuyama Corporation; and "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs.
[0034] The range of the specific surface area and average particle size of the optional inorganic filler (A-2) may be the same as that of the white inorganic pigment (A-1). The optional inorganic filler (A-2) may be used alone or in combination of two or more kinds.
[0035] From the viewpoint of improving moisture resistance and dispersibility, it is preferable that the (A-2) optional inorganic filler is treated with a surface treatment agent. Examples of the surface treatment agent include the same as the surface treatment agent for the (A-1) white inorganic pigment. The degree of surface treatment of the (A-2) optional inorganic filler with the surface treatment agent can be the same as that of the (A-1) white inorganic pigment.
[0036] The amount of the optional inorganic filler (A-2) contained in the resin composition, from the viewpoint of effectively increasing the reflectance of the cured product and from the viewpoint of effectively increasing the processability during cavity formation, is preferably 60 mass% or less, more preferably 50 mass% or less, and even more preferably 40 mass% or less, relative to 100 mass% of the nonvolatile components in the resin composition, and may be, for example, 0 mass% or more, 1 mass% or more, 5 mass% or more, 10 mass% or more, 15 mass% or more, 20 mass% or more, etc.
[0037] The amount of (A) inorganic filler contained in the resin composition (i.e., the total amount of (A-1) white inorganic pigment and (A-2) optional inorganic filler) is, from the viewpoint of effectively increasing the reflectance of the cured product and effectively increasing the processability during cavity formation, preferably 20 mass% or more, more preferably 30 mass% or more, even more preferably 40 mass% or more, and is preferably 70 mass% or less, more preferably 65 mass% or less, even more preferably 60 mass% or less, and particularly preferably 58 mass% or less, based on 100 mass% of non-volatile components in the resin composition.
[0038] The mass ratio of the optional inorganic filler (A-2) to the white inorganic pigment (A-1) (mass of component (A-2) / mass of component (A-1)) is, from the viewpoint of effectively increasing the reflectance of the cured product and effectively increasing the processability during cavity formation, preferably 0 or more, more preferably 0.1 or more, even more preferably 0.2 or more, and particularly preferably 0.8 or more; and is preferably 4.0 or less, more preferably 3.0 or less, even more preferably 2.0 or less, and particularly preferably 1.5 or less.
[0039] <(B) Thermosetting resin> Since the resin composition has thermosetting properties, it usually contains a thermosetting resin (B). The thermosetting resin (B) may be used alone or in combination of two or more. In particular, from the viewpoint of effectively increasing the reflectance of the cured product and effectively increasing the processability during cavity formation, it is preferable that the thermosetting resin (B) contains an epoxy resin (B-1).
[0040] The (B-1) epoxy resin means a curable resin having an epoxy group. The (B-1) epoxy resin may be used alone or in combination of two or more kinds.
[0041] Examples of the epoxy resin (B-1) include bixylenol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, hydrogenated bisphenol A type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol novolac type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, glycidylamine type epoxy resin, glycidyl Examples of the epoxy resins include ester type epoxy resins, cresol novolac type epoxy resins, phenol aralkyl type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, isocyanurate type epoxy resins, phenolphthalimidine type epoxy resins, and phenolphthalein type epoxy resins.
[0042] The resin composition preferably contains, as the epoxy resin (B-1), an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule relative to 100% by mass of the non-volatile components of the epoxy resin (B-1) is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.
[0043] Epoxy resins include epoxy resins that are solid at a temperature of 25° C. (hereinafter sometimes referred to as “solid epoxy resins”) and epoxy resins that are liquid at a temperature of 25° C. (hereinafter sometimes referred to as “liquid epoxy resins”). The resin composition may contain only a solid epoxy resin as the (B-1) epoxy resin, or may contain only a liquid epoxy resin, or may contain a combination of a solid epoxy resin and a liquid epoxy resin.
[0044] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.
[0045] Preferred solid epoxy resins include bixylenol type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, naphthol novolac type epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, phenol aralkyl type epoxy resins, tetraphenylethane type epoxy resins, phenolphthalimidine type epoxy resins, and phenolphthalein type epoxy resins.
[0046] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene type epoxy resins) manufactured by DIC Corporation; and "EXA-73" manufactured by DIC Corporation. 11", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000L", "NC3000FH", "NC3100" (biphenyl type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN475V" manufactured by Nippon Steel Chemical & Material Co., Ltd. (Naphthalene type epoxy resin); "ESN485" (Naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (Dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (Bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YL6121" (Biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX8800" (Anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX77" manufactured by Mitsubishi Chemical Co., Ltd. Examples of epoxy resins include "PG-100" (phenol aralkyl type epoxy resin), "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals, "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical, "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical, "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical, "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical, and "WHR991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. These may be used alone or in combination of two or more types.
[0047] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.
[0048] Preferred liquid epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, hydrogenated bisphenol A type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins having an ester skeleton, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, and epoxy resins having a butadiene structure.
[0049] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "828EL", "jER828EL", "825", and "Epicoat 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630", "630LSD", and "604" (glycidylamine type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA Corporation; and "EP-3950L" and "EP-3980S" (glycidylamine type epoxy resins) manufactured by ADEKA Corporation. Examples of such epoxy resins include "EP-4088S" (dicyclopentadiene type epoxy resin) manufactured by ADEKA Corporation; "ZX1059" (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical & Material Corporation; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase Chemtex Corporation; "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton) manufactured by Daicel Corporation; "PB-3600" manufactured by Daicel Corporation, "JP-100" and "JP-200" (epoxy resin having a butadiene structure) manufactured by Nippon Steel Chemical & Material Corporation; "ZX1658" and "ZX1658GS" (1,4-glycidylcyclohexane type epoxy resin) manufactured by Nippon Steel Chemical & Material Corporation, and "YX8000" (hydrogenated bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation. These may be used alone or in combination of two or more types.
[0050] The (B-1) epoxy resin may be any one of a solid epoxy resin, a liquid epoxy resin, or a combination thereof. From the viewpoint of significantly obtaining the desired effects of the present invention, however, it preferably contains a solid epoxy resin, and is particularly preferably a combination of a solid epoxy resin and a liquid epoxy resin.
[0051] When a solid epoxy resin and a liquid epoxy resin are used in combination as the (B-1) epoxy resin, the mass ratio thereof (solid epoxy resin:liquid epoxy resin) is preferably 20:1 to 1:20, more preferably 10:1 to 1:10, and particularly preferably 3:1 to 1:3.
[0052] The epoxy equivalent of the (B-1) epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 1,000 g / eq., even more preferably 80 g / eq. to 500 g / eq., and even more preferably 100 g / eq. to 300 g / eq. The epoxy equivalent is the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.
[0053] The weight average molecular weight (Mw) of the epoxy resin (B-1) is preferably 100 to 5,000, more preferably 250 to 3,000, and even more preferably 400 to 1500. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.
[0054] From the viewpoint of effectively increasing the reflectance of the cured product and effectively increasing the processability during cavity formation, the amount of the epoxy resin (B-1) contained in the resin composition is preferably 1 mass% or more, more preferably 5 mass% or more, even more preferably 10 mass% or more, particularly preferably 15 mass% or more, and is preferably 50 mass% or less, more preferably 40 mass% or less, even more preferably 35 mass% or less, and particularly preferably 30 mass% or less, based on 100 mass% of non-volatile components in the resin composition.
[0055] The amount of the (B-1) epoxy resin contained in the resin composition is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, particularly preferably 40% by mass or more, and is preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 65% by mass or less, particularly preferably 60% by mass or less, when the resin component in the resin composition is taken as 100% by mass, from the viewpoint of effectively increasing the reflectance of the cured product and effectively increasing the processability during cavity formation. Unless otherwise specified, the resin component of the resin composition refers to the components excluding the (A) inorganic filler among the non-volatile components of the resin composition.
[0056] When the (B) thermosetting resin contains the (B-1) epoxy resin, the (B) thermosetting resin may further contain a (B-2) curing agent. The (B-2) curing agent has a function of reacting with the (B-1) epoxy resin to cure the resin composition. The (B-2) curing agent may be used alone or in combination of two or more.
[0057] The (B-2) curing agent is not particularly limited, and examples thereof include phenol-based curing agents, carbodiimide-based curing agents, acid anhydride-based curing agents, amine-based curing agents, benzoxazine-based curing agents, cyanate ester-based curing agents, thiol-based curing agents, etc. From the viewpoint of significantly obtaining the desired effects of the present invention, it is preferable that the (B-2) curing agent contains a phenol-based curing agent.
[0058] The phenol-based curing agent is a curing agent having two or more phenolic hydroxyl groups in one molecule, and examples thereof include bisphenol-based curing agents, biphenyl-type phenol-based curing agents, naphthalene-type phenol-based curing agents, phenol novolac-type phenol-based curing agents, naphthylene ether-type phenol-based curing agents, triazine skeleton-containing phenol-based curing agents, polyphenylene ether-type phenol-based curing agents, phenol aralkyl-type phenol-based curing agents, cresol novolac-type phenol-based curing agents, bisphenol-type phenol-based curing agents, etc. Among them, bisphenol-based curing agents are preferred, more preferably bisphenol-based curing agents selected from bisphenol compounds having fluorine atoms, bisphenol compounds having an alicyclic structure, and bisphenol compounds having a fluorene skeleton, further preferably bisphenol compounds having fluorine atoms, and particularly preferably bisphenol AF.
[0059] Commercially available phenol-based hardeners include, for example, "BiS-AF," "BiSOFP-A," "BiS-Z," and "BiSOC-FL," manufactured by Central Glass Co., Ltd.
[0060] The carbodiimide-based curing agent is a curing agent having two or more carbodiimide structures in one molecule, and examples of the curing agent include aliphatic biscarbodiimides such as tetramethylene-bis(t-butylcarbodiimide) and cyclohexane bis(methylene-t-butylcarbodiimide); aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide); Examples of polycarbodiimides include aromatic polycarbodiimides such as poly(methylenediphenylenecarbodiimide), poly(naphthylenecarbodiimide), poly(tolylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), and poly[methylenebis(methylphenylene)carbodiimide].
[0061] Commercially available carbodiimide curing agents include, for example, "Carbodilite V-02B", "Carbodilite V-03", "Carbodilite V-04K", "Carbodilite V-07", and "Carbodilite V-09" manufactured by Nisshinbo Chemical Inc.; and "Stavaxol P", "Stavaxol P400", and "Hi-Kasil 510" manufactured by Rhein Chemie.
[0062] The acid anhydride curing agent is a curing agent having one or more carboxylic acid anhydride groups (-CO-O-CO-) in one molecule, and examples thereof include phthalic anhydride, pyromellitic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 3,3',4,4'-diphenylethertetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, methylene-4,4' aromatic acid anhydride-based hardeners such as tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, cyclopentanetetracarboxylic dianhydride, cyclohexane-1,2,4,5-tetracarboxylic dianhydride, and the like; and polymeric anhydride-based hardeners such as styrene / maleic anhydride copolymer, and alkyl (meth)acrylate / styrene / maleic anhydride copolymer. Commercially available acid anhydride curing agents include "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by New Japan Chemical Co., Ltd., "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation, and "HN-2200" and "HN-5500" manufactured by Hitachi Chemical Co., Ltd.
[0063] The amine-based curing agent is a curing agent having two or more amino groups, and examples thereof include aliphatic amines, polyether amines, alicyclic amines, and aromatic amines. Among them, aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based curing agent is preferably a primary amine or a secondary amine, and more preferably a primary amine. Specific examples of the amine-based curing agent include 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxyphenyl)propane, and the like. propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, and the like. As the amine-based curing agent, commercially available products may be used, and examples thereof include "SEIKACURE-S" manufactured by Seika Corporation, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.
[0064] Specific examples of benzoxazine-based curing agents include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Corporation; "HFB2006M" manufactured by Showa Polymer Co., Ltd.; and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.
[0065] Examples of the cyanate ester curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (both of which are phenol novolac-type multifunctional cyanate ester resins), "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.
[0066] The thiol-based curing agent is a curing agent having two or more mercapto groups, and examples thereof include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.
[0067] The reactive group equivalent of the (B-2) curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The reactive group equivalent is the mass of the curing agent per equivalent of reactive group. For example, in the case of a phenol-based curing agent, the reactive group is a phenolic hydroxyl group. In the case of an acid anhydride-based curing agent, one equivalent of a carboxylic anhydride group (-CO-O-CO-) corresponds to two equivalents of reactive group.
[0068] From the viewpoint of obtaining the effects of the present invention prominently, the amount of the (B-2) curing agent contained in the resin composition is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 1% by mass or more, particularly preferably 3% by mass or more, and is preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 25% by mass or less, and particularly preferably 20% by mass or less, based on 100% by mass of non-volatile components in the resin composition.
[0069] From the viewpoint of obtaining the effects of the present invention prominently, the amount of the (B-2) curing agent contained in the resin composition is, when the resin component in the resin composition is taken as 100% by mass, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 1% by mass or more, particularly preferably 5% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, and particularly preferably 20% by mass or less.
[0070] <(C) Thermoplastic resin> The resin composition may further contain a thermoplastic resin (C) in combination with the above-mentioned components. The thermoplastic resin (C) may be used alone or in combination of two or more kinds.
[0071] Examples of the thermoplastic resin (C) include phenoxy resin, polyvinyl acetal resin, acrylic resin, polyolefin resin, polybutadiene resin, polyimide resin, polyamideimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polyetherimide resin, polycarbonate resin, polyetheretherketone resin, and polyester resin. Among these, from the viewpoint of obtaining the effects of the present invention remarkably, a resin selected from phenoxy resin, acrylic resin, and polyphenylene ether resin is preferable, and phenoxy resin is particularly preferable.
[0072] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group. The phenoxy resin may be used alone or in combination of two or more. Specific examples of phenoxy resins include "1256" and "4250" (both of which are phenoxy resins containing a bisphenol A skeleton), "YX8100" (phenoxy resin containing a bisphenol S skeleton), and "YX6954" (phenoxy resin containing a bisphenol acetophenone skeleton) manufactured by Mitsubishi Chemical Corporation, "FX280" and "FX293" manufactured by Nippon Steel Chemical & Material Co., Ltd., and "YX7200B35", "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", and "YL7482" manufactured by Mitsubishi Chemical Corporation.
[0073] Examples of polyvinyl acetal resins include polyvinyl formal resins and polyvinyl butyral resins, and polyvinyl butyral resins are preferred.Specific examples of polyvinyl acetal resins include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd., and S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.
[0074] The acrylic resin refers to a polymer obtained by polymerizing a monomer component including a (meth)acrylic acid ester monomer. The monomer components constituting the acrylic resin may contain, in addition to the (meth)acrylic acid ester monomer, a (meth)acrylamide monomer, a styrene monomer, a functional group-containing monomer, or the like as copolymerization components. Specific examples of acrylic resins include "ARUFON UP-1000", "ARUFON UP-1010", "ARUFON UP-1020", "ARUFON UP-1021", "ARUFON UP-1061", "ARUFON UP-1080", "ARUFON UP-1110", "ARUFON UP-1170", "ARUFON UP-1190", "ARUFON UP-1500", "ARUFON UH-2000", "ARUFON UH-2041", "ARUFON UH-2190", "ARUFON UHE-2012", "ARUFON UC-3510", "ARUFON UG-4010", "ARUFON US-6100", and "ARUFON US-6170", all manufactured by Toagosei Co., Ltd. These may be used alone or in combination of two or more.
[0075] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin-based elastomers such as polypropylene and ethylene-propylene block copolymer.
[0076] Examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxy group-containing polybutadiene resins, phenolic hydroxy group-containing polybutadiene resins, carboxy group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, urethane group-containing polybutadiene resins, polyphenylene ether-polybutadiene resins, and the like.
[0077] Specific examples of polyimide resins include "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd. Specific examples of polyimide resins also include modified polyimides such as linear polyimides obtained by reacting bifunctional hydroxyl-terminated polybutadiene, a diisocyanate compound, and a tetrabasic acid anhydride (polyimides described in JP-A-2006-37083), and polysiloxane skeleton-containing polyimides (polyimides described in JP-A-2002-12667 and JP-A-2000-319386, etc.).
[0078] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.
[0079] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.
[0080] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers, Inc.
[0081] Specific examples of polyphenylene ether resins include oligophenylene ether-styrene resins "OPE-2St1200" and "OPE-2St2200" manufactured by Mitsubishi Gas Chemical Co., Inc., and "NORYL SA90" manufactured by SABIC. Specific examples of polyetherimide resins include "Ultem" manufactured by GE.
[0082] Examples of polycarbonate resins include hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, and urethane group-containing carbonate resins. Specific examples of polycarbonate resins include "FPC0220" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002" and "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diol) manufactured by Kuraray Co., Ltd. Specific examples of polyether ether ketone resins include "Sumiploy K" manufactured by Sumitomo Chemical Co., Ltd. Examples of polyester resins include polyethylene terephthalate resins.
[0083] The weight average molecular weight of the thermoplastic resin (C) is preferably 8,000 or more, more preferably 10,000 or more, and even more preferably 20,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less, and even more preferably 60,000 or less. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.
[0084] The thermoplastic resin (C) is preferably a thermoplastic resin that, when formed into a film having a thickness of 20 μm, has a transmittance of 80% or more for light having a wavelength of 460 nm that is incident perpendicularly to the film surface.
[0085] From the viewpoint of effectively increasing the reflectance of the cured product and from the viewpoint of effectively increasing the processability during cavity formation, the amount of the thermoplastic resin (C) contained in the resin composition is, relative to 100 mass% of the non-volatile components in the resin composition, preferably 0.1 mass% or more, more preferably 1.0 mass% or more, even more preferably 5 mass% or more, even more preferably 10 mass% or more, particularly preferably 15 mass% or more, and is preferably 50 mass% or less, more preferably 45 mass% or less, even more preferably 40 mass% or less, and particularly preferably 35 mass% or less.
[0086] From the viewpoint of effectively increasing the reflectance of the cured product and effectively increasing the processability during cavity formation, the amount of the (C) thermoplastic resin contained in the resin composition is preferably 1 mass% or more, more preferably 10 mass% or more, even more preferably 20 mass% or more, particularly preferably 30 mass% or more, and is preferably 75 mass% or less, more preferably 65 mass% or less, even more preferably 60 mass% or less, and particularly preferably 55 mass% or less, based on 100 mass% of the resin component in the resin composition.
[0087] <(D) Curing accelerator> The resin composition may further contain a curing accelerator (D) in combination with the above-mentioned components. The curing accelerator (D) has a function of accelerating the curing reaction of the thermosetting resin (B) such as the epoxy resin (B-1). The curing accelerator (D) may be used alone or in combination of two or more kinds.
[0088] Examples of the (D) curing accelerator include phosphorus-based curing accelerators, imidazole-based curing accelerators, amine-based curing accelerators, guanidine-based curing accelerators, metal-based curing accelerators, etc. Among these, as the (D) curing accelerator, from the viewpoint of achieving a higher reflectance, phosphorus-based curing accelerators and imidazole-based curing accelerators are preferred, and phosphorus-based curing accelerators are more preferred.
[0089] From the viewpoint of achieving a higher reflectance, the phosphorus-based curing accelerator preferably contains one or more members selected from the group consisting of phosphonium salts and phosphines.
[0090] Examples of the phosphonium salt include aliphatic phosphonium salts such as tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitate, tetrabutylphosphonium hydrogenhexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butylmethylphosphonium tetraphenylborate; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, and the like. Examples of aromatic phosphonium salts include aromatic phosphonium salts such as phenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, p-tolyltriphenylphosphonium tetra-p-tolylborate, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate.
[0091] Examples of phosphines include aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine; dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, and tris(2,5-dimethylphenyl)phosphine. tris(2,6-dimethylphenyl)phosphine, tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2- Examples of aromatic phosphines include bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; and aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct.
[0092] As the phosphorus-based curing accelerator, commercially available products may be used, for example, "TBP-DA" manufactured by Hokko Chemical Industry Co., Ltd.
[0093] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2, 4-Diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-furan Examples of the imidazole compounds include imidazole compounds such as 2-ethyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins. Of these, 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole are preferred.
[0094] As the imidazole-based curing accelerator, commercially available products may be used, for example, "P200-H50" manufactured by Mitsubishi Chemical Corporation, and "1B2PZ-10M" manufactured by Shikoku Kasei Co., Ltd.
[0095] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, with 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene being preferred.
[0096] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene. Examples of such biguanide include o-[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. Of these, dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene are preferred.
[0097] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.
[0098] From the viewpoint of significantly obtaining the effects of the present invention, the amount of the (D) curing accelerator contained in the resin composition is, when the non-volatile components in the resin composition are taken as 100 mass%, preferably 5 mass% or less, more preferably 3 mass% or less, even more preferably 1 mass% or less, and particularly preferably 0.8 mass% or less, for example, 0 mass% or more, 0.001 mass% or more, preferably 0.01 mass% or more, more preferably 0.05 mass% or more, and particularly preferably 0.1 mass% or more.
[0099] From the viewpoint of significantly obtaining the effects of the present invention, the amount of the curing accelerator (D) contained in the resin composition is, relative to 100 mass% of the resin component in the resin composition, preferably 0.01 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.5 mass% or more, particularly preferably 1.0 mass% or more, and is preferably 10 mass% or less, more preferably 7 mass% or less, even more preferably 4 mass% or less, and particularly preferably 2 mass% or less.
[0100] <(E) Optional Additives> The resin composition may further contain (E) an optional additive as a non-volatile component in combination with the above-mentioned components. (E) The optional additive may be, for example, an organic filler such as rubber particles; a leveling agent such as a silicone-based leveling agent or an acrylic polymer-based leveling agent; a thickener such as bentone or montmorillonite; an antifoaming agent such as a silicone-based antifoaming agent, an acrylic-based antifoaming agent, a fluorine-based antifoaming agent, or a vinyl resin-based antifoaming agent; an ultraviolet absorbing agent such as a benzophenone-based ultraviolet absorbing agent, a benzotriazole-based ultraviolet absorbing agent, or a salicylic acid-based ultraviolet absorbing agent; an adhesion improving agent such as urea silane; an adhesion imparting agent such as a triazole-based adhesion imparting agent, a tetrazole-based adhesion imparting agent, or a triazine-based adhesion imparting agent; an antioxidant such as a hindered phenol-based antioxidant; a fluorescent brightening agent such as a stilbene derivative; Examples of the additives include surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate ester-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; and stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers. (E) Optional additives may be used alone or in combination of two or more at any ratio. The content of (E) optional additives can be appropriately determined by those skilled in the art.
[0101] <(F) Organic solvent> The resin composition may further contain an arbitrary organic solvent as a volatile component in addition to the non-volatile components described above. As the (F) organic solvent, a known one can be appropriately used, and the type is not particularly limited. As the (F) organic solvent, for example, ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, etc.; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, etc.; alcohol-based solvents such as methanol, ethanol, propanol, butanol, ethylene glycol, etc.; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, methyl methoxypropionate, etc. Examples of the organic solvent include ether ester solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butyl carbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. The organic solvent (F) may be used alone or in combination of two or more in any ratio.
[0102] The amount of the (F) organic solvent contained in the resin composition is not particularly limited, but when all components in the resin composition are taken as 100 mass%, it can be, for example, 60 mass% or less, 40 mass% or less, 30 mass% or less, 20 mass% or less, 15 mass% or less, 10 mass% or less, 5 mass% or less, etc.
[0103] <Method of producing resin composition> The resin composition can be produced, for example, by adding and mixing the above-mentioned components in any preparation vessel in any order and / or all or part of them at the same time. In the process of adding and mixing the components, the temperature can be appropriately set, and heating and / or cooling can be performed temporarily or throughout. In the process of adding and mixing or thereafter, the resin composition can be stirred or shaken using a stirring or shaking device such as a mixer to disperse the resin composition uniformly. In addition, degassing can be performed under low pressure conditions such as under vacuum at the same time as stirring or shaking.
[0104] <Resin sheet> From the viewpoint of easily and efficiently forming the cured layer, the resin composition is preferably prepared in the form of a resin sheet including a resin composition layer formed from the resin composition. In one embodiment, the resin sheet includes a support and a resin composition layer provided on the support.
[0105] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.
[0106] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0107] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.
[0108] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.
[0109] In addition, as the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "PET501010", "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.
[0110] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.
[0111] The thickness range of the resin composition layer contained in the resin sheet may be the same as the thickness range of the cured layer described below.
[0112] In one embodiment, the resin sheet may further include other layers as necessary. Examples of such other layers include a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, adhesion of dirt and the like to the surface of the resin composition layer and scratches can be suppressed.
[0113] The resin sheet can be produced, for example, by preparing a liquid resin composition as is or a resin varnish by dissolving the resin composition in an organic solvent, applying this onto a support using a die coater or the like, and then drying to form a resin composition layer.
[0114] The organic solvent may be the same as the organic solvent described as a component of the resin composition. The organic solvent may be used alone or in combination of two or more kinds.
[0115] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of organic solvent in the resin composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the boiling point of the organic solvent in the resin composition (resin varnish), for example, when a resin composition (resin varnish) containing 30 mass % to 60 mass % of organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.
[0116] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.
[0117] [2.2. Step of preparing a resin composition layer (I-1)] In step (I-1), a resin composition layer is prepared. Usually, the resin composition layer is prepared by being provided on a suitable substrate. There is no limitation on the substrate, and for example, a circuit board having an insulating layer and a conductor layer can be used. Preferable circuit boards include, for example, a circuit board having a conductor circuit formed of a conductor layer on at least a part of the surface; a circuit board having an insulating layer, a conductor layer formed on the insulating layer, and a solder resist layer formed on the conductor layer; and the like.
[0118] The resin composition layer may be provided by, for example, a compression molding method. The resin composition layer may be provided by, for example, applying the resin composition onto a substrate. From the viewpoint of smoothly manufacturing a printed wiring board, it is preferable to provide the resin composition layer by laminating a resin sheet onto a substrate. This lamination is usually performed so that the resin composition layer of the resin sheet and the substrate are bonded. The substrate and the resin sheet can be laminated, for example, by thermocompression bonding the resin sheet to the substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the substrate (hereinafter also referred to as "thermocompression bonding member") include a heated metal plate (such as a SUS mirror plate) or a metal roll (SUS roll). It is preferable to press the thermocompression bonding member through an elastic material such as heat-resistant rubber so that the resin sheet sufficiently follows the surface unevenness of the substrate, rather than directly pressing the resin sheet.
[0119] The substrate and the resin sheet may be laminated by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably carried out under reduced pressure conditions of 26.7hPa or less.
[0120] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.
[0121] After lamination, the laminated resin sheet may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.
[0122] The thickness range of the resin composition layer thus provided may be the same as the thickness range of the cured layer described below.
[0123] [2.3. Step of thermally curing the resin composition layer (I-2)] After providing the resin composition layer in step (I-1), a step (I-2) of thermally curing the resin composition layer is carried out to obtain a cured layer formed of a cured product of the resin composition. The thermal curing conditions of the resin composition layer may vary depending on the type of resin composition, etc. In one example, the curing temperature may be preferably 120°C to 240°C, more preferably 130°C to 220°C, and even more preferably 150°C to 210°C. The curing time may be preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.
[0124] Step (I) may include a step of preheating the resin composition at a temperature lower than the curing temperature before curing the resin composition in step (I-2). In this step, for example, prior to thermal curing of the resin composition, the resin composition may be preheated for 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes) at a temperature of 50°C or more and less than 120°C (preferably 60°C or more and 115°C or less, more preferably 70°C or more and 110°C or less).
[0125] Fig. 1 is a cross-sectional view showing a schematic diagram of a cured layer 20 prepared in step (I) to explain a method for producing a printed wiring board according to one embodiment of the present invention. As shown in Fig. 1 as an example, according to step (I), a cured layer 20 is usually provided on a substrate 10. Fig. 1 shows a state in which a support (not shown) of a resin sheet has been removed, but a support may be present on the cured layer 20 prepared in step (I).
[0126] Thickness T of the hardened layer 20 20 is preferably 5 μm or more, more preferably 10 μm or more, particularly preferably 15 μm or more, and is preferably 150 μm or less, more preferably 130 μm or less, particularly preferably 120 μm or less. 20 When the thickness T of the cured layer 20 is equal to or greater than the lower limit of the range, the light reflectance of the cured layer 20 can be effectively increased. 20 When the thickness T of the cured layer 20 is equal to or less than the upper limit of the above range, the printed wiring board can be made thinner. 20 When the thickness is within the above range, it is possible to effectively improve the workability of the cavity.
[0127] [3. Step (II) of forming a cavity in the hardened layer] After preparing the hardened layer in step (I), step (II) is performed in which the hardened layer is subjected to a sandblasting process to form cavities. In the sandblasting process, abrasive grains are usually ejected from a nozzle and collided with the hardened layer. In general, the abrasive grains are ejected by air at an appropriate pressure. The hardened layer is scraped by the collision of the abrasive grains, so that cavities can be formed in the hardened layer. The abrasive grains may be ejected without containing liquid (dry blasting process) or in the form of a slurry containing liquid (wet blasting process).
[0128] The cured product of the thermosetting resin composition can generally have high hardness. Therefore, the cured layer prepared in the above-mentioned step (I) can be smoothly scraped by the collision of abrasive grains. Therefore, it is possible to form a cavity with high precision by sandblasting, and excellent processability can be achieved. The above-mentioned advantages of the thermosetting resin composition are in contrast to the case where a photosensitive resin composition is used. That is, since the cured product of the photosensitive resin composition is generally soft, it is difficult to scrape it accurately by the collision of abrasive grains. In contrast, in the present embodiment in which the thermosetting resin composition is adopted, it is possible to achieve better processability than the case where a photosensitive resin composition is used.
[0129] In order to selectively form cavities at desired positions, the sandblasting process is usually performed with a mask placed on the hardened layer. Generally, the mask has an opening at the position where the cavity is to be formed. Therefore, at the position where the opening is formed, the abrasive particles collide with the hardened layer, and the hardened layer is scraped. On the other hand, at the position where the opening is not formed, the abrasive particles are blocked by the mask and do not collide with the hardened layer, so the hardened layer is not scraped. Therefore, a cavity can be formed at the position of the opening that is not covered by the mask. When performing the sandblasting process using a mask in this way, the step (II) may include a step (II-1) of placing the mask on the hardened layer and a step (II-2) of spraying the abrasive particles into the hardened layer through the opening of the mask.
[0130] [3.1. Step of placing a mask on the hardened layer (II-1)] In step (II-1), a mask having an opening is placed on the cured layer. Any mask capable of forming a cavity can be used. Among them, it is preferable to use a patterned dry film as the mask, since the shape and size of the opening can be accurately controlled.
[0131] In the case where a patterned dry film is provided on the cured layer as a mask, the step (II-1) may, for example, laminating a dry film on the cured layer; and A process of exposing and developing the dry film using a photomask to obtain a patterned dry film. may include.
[0132] FIG. 2 is a cross-sectional view showing a state where a dry film 30 is provided on the curing layer 20 in step (II-1) to explain a method for manufacturing a printed wiring board according to an embodiment of the present invention. As shown in FIG. 2 as an example, step (II-1) may include a step of laminating the dry film 30 on the curing layer 20. The lamination conditions of the curing layer 20 and the dry film 30 may be the same as the lamination conditions of the substrate and the resin sheet described above. FIG. 2 shows an example in which lamination is performed so that the dry film 30 is in contact with the surface 20U of the curing layer 20 on the side opposite to the substrate 10. However, if a support (not shown) of the resin sheet is present on the curing layer 20, the dry film 30 may be laminated on the curing layer 20 via this support.
[0133] The dry film 30 may be one that can obtain a patterned dry film by exposure and development. Among them, a film formed of a material that is resistant to sandblasting is preferable. For example, the dry film 30 may be a photosensitive film formed of a photoresist composition. Examples of such a dry film 30 include dry films formed of resins such as novolac resins and acrylic resins.
[0134] Thickness T of dry film 30 30From the viewpoint of improving the processability of the cavity, the thickness is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more, and is preferably 100 μm or less, more preferably 70 μm or less, and even more preferably 50 μm or less.
[0135] FIG. 3 is a cross-sectional view showing a typical exposure process of the dry film 30 in step (II-1) to explain a method for producing a printed wiring board according to an embodiment of the present invention. As shown in FIG. 3 as an example, after the dry film 30 is laminated on the curing layer 20, the dry film 30 is exposed to light using a photomask 40. In this exposure process, the dry film 30 is usually irradiated with active energy rays (not shown) through a photomask 40 having an appropriate pattern. Here, an example is shown in which the exposed portion of the dry film 30 is photocured by the exposure process. The exposed portion refers to the portion exposed to the light of the exposure process unless otherwise specified. Examples of active energy rays include ultraviolet rays, visible light rays, electron beams, and X-rays, and ultraviolet rays are preferred. The dose and time of exposure of the ultraviolet rays can be appropriately set according to the dry film 30. Examples of the exposure method include a contact exposure method in which the photomask 40 is brought into close contact with the dry film 30 and exposed to light, and a non-contact exposure method in which the photomask 40 is not brought into close contact with the dry film 30 and exposed to light using parallel light.
[0136] FIG. 4 is a cross-sectional view showing a schematic state after the dry film 30 is subjected to a development process in step (II-1) to explain a method for manufacturing a printed wiring board according to an embodiment of the present invention. After the exposure process, the dry film 30 is subjected to a development process. As shown in FIG. 4, one of the exposed and non-exposed parts of the dry film 30 is removed by the development process, so that a patterned dry film 50 having an opening 51 is obtained. Here, an example is shown and explained in which the non-exposed part of the dry film 30 is removed by the development process to obtain a patterned dry film 50 having an opening 51. The non-exposed part refers to a part that is not exposed to the light of the exposure process, unless otherwise specified. The development may be performed by either wet development or dry development. Examples of the development method include a dip method, a paddle method, a spray method, a brushing method, and a scraping method.
[0137] [3.2. Step of spraying abrasive particles onto the hardened layer (II-2)] 4, after a patterned dry film 50 is placed on the cured layer 20 as a mask in step (II-1), a sandblasting process is performed on the cured layer 20 using the patterned dry film 50 as a mask in step (II-2). Specifically, in step (II-2), abrasive grains (not shown) are sprayed onto the cured layer 20 through openings 51 in the patterned dry film 50.
[0138] FIG. 5 is a cross-sectional view showing a schematic state after the sandblasting process is performed in step (II-2) to explain the method for manufacturing a printed wiring board according to one embodiment of the present invention. In the portion not covered by the patterned dry film 50 (the portion exposed to the opening 51), the abrasive grains collide and the hardened layer 20 is scraped off. On the other hand, in the portion covered by the patterned dry film 50, the hardened layer 20 is protected by the patterned dry film 50, so that the hardened layer 20 is not scraped off. Therefore, as shown in FIG. 5, only the portion of the hardened layer 20 exposed to the opening 51 is selectively scraped off by the collision of the abrasive grains, so that a cavity 60 is formed in the hardened layer 20. Usually, the formed cavity 60 can have the same planar shape as the opening 51. The planar shape refers to the shape seen from the thickness direction unless otherwise specified.
[0139] The sandblasting may be either a dry blasting process in which abrasive grains are blasted, or a wet blasting process in which a slurry containing abrasive grains and a liquid is blasted. As the sandblasting, a dry blasting process is preferred from the viewpoint of effectively improving the workability of the cavity.
[0140] Examples of the abrasive grains include particles mainly made of inorganic compounds such as silica and glass; metal compounds such as steel, stainless steel, zinc, and copper; ceramics such as garnet, zirconia, silicon carbide, alumina, and boron carbide; and materials such as dry ice. Among them, from the viewpoint of significantly obtaining the desired effects of the present invention, inorganic compound particles and ceramic particles are preferred, and any of alumina particles, silicon carbide particles, and silica particles is preferred. As for the silica, crystalline silica is preferred.
[0141] The abrasive grains may be commercially available products, such as "DAW-03" manufactured by Denka Co., Ltd., "AY2-75" (alumina) manufactured by Nippon Steel Chemical & Material Co., Ltd., "GP#4000" and "SER-A06" (silicon carbide) manufactured by Shinano Electric Refining Co., Ltd., "IMSIL A-8" (crystalline silica) manufactured by Tatsumori Co., Ltd., and "Fuji Random WA" (fused alumina) manufactured by Fuji Manufacturing Co., Ltd.
[0142] From the viewpoint of improving the workability of small-sized cavities, the modified Mohs hardness of the abrasive grains used in the sandblasting treatment is preferably 5 or more, more preferably 6 or more, and particularly preferably 7 or more. The upper limit value can usually be 15 or less. The modified Mohs hardness of the abrasive grains can be measured using a Mohs hardness tester.
[0143] The average particle size of the abrasive grains is preferably 0.5 μm or more, more preferably 1.0 μm or more, more preferably 2.0 μm or more, and preferably 50 μm or less, more preferably 30 μm or less, even more preferably 20 μm or less, and particularly preferably 15 μm or less. When the average particle size of the abrasive grains is within the above range, the workability of a small-sized cavity can be improved. For example, the processing time of the cavity can be shortened, the blowback of the abrasive grains can be suppressed to suppress the grinding of the mask, and the gradient angle of the wall surface of the cavity can be increased. The average particle size of the abrasive grains can be measured, for example, by observation with a scanning electron microscope, and the details can be determined by the method described in JP-A-2008-41932.
[0144] From the viewpoint of improving the processability of the cavity, the average particle size R1 of the abrasive grains is preferably larger than the average particle size R2 of the white inorganic pigment (A-1) contained in the hardened layer. Also, from the viewpoint of improving the processability of the cavity, the ratio R1 / R2 of the average particle size R1 of the abrasive grains to the average particle size R2 of the white inorganic pigment (A-1) is preferably 3 or more, more preferably 5 or more, particularly preferably 10 or more, and is preferably 100 or less, more preferably 80 or less, particularly preferably 50 or less.
[0145] The average grain size R1 of the abrasive grains is set to the thickness T of the hardened layer in order to improve the workability of the cavity. 20 The thickness of the hardened layer T is preferably smaller than 20 Ratio of the average grain size R1 of the abrasive grains to R1 / T 20 is preferably 0.01 or more, more preferably 0.02 or more, particularly preferably 0.04 or more, and is preferably 0.80 or less, more preferably 0.50 or less, particularly preferably 0.30 or less.
[0146] The pressure (processing pressure) for spraying the abrasive grains is preferably 0.05 MPa or more, more preferably 0.1 MPa or more, and even more preferably 0.15 MPa or more, and is preferably 1 MPa or less, more preferably 0.8 MPa or less, and even more preferably 0.5 MPa or less, from the viewpoint of improving the processability of the cavity and forming the cavity in a short time. Here, the processing pressure is the value at the surface of the hardened layer.
[0147] [3.3. Mask removal process (II-3)] After the cavity is formed, the mask may remain on the surface of the cured layer. For example, when the above-mentioned patterned dry film is used as a mask, the patterned dry film may be scraped off by collision with the abrasive grains, and as shown in the example of FIG. 5, a part of the patterned dry film may remain on the cured layer. Therefore, a step of removing the mask may be performed.
[0148] There is no limitation on the method of removing the mask. For example, when a patterned dry film is used as a mask, the patterned dry film may be removed by contacting the film with a removal solution capable of dissolving the patterned dry film and dissolving it. Examples of the contact method include, but are not limited to, a dipping method, a spraying method, and a coating method.
[0149] [4. Optional process] The method for producing a printed wiring board according to one embodiment of the present invention may further include any optional steps in combination with the steps described above.
[0150] For example, the method for producing a printed wiring board may include a step of peeling off the support. There is no limitation on the timing of peeling off the support. Thus, the support may be peeled off between step (I-1) and step (I-2), between step (I-2) and step (II), between step (II-1) and step (II-2), or after step (II-2).
[0151] For example, the method for manufacturing a printed wiring board may include a step of arranging a light source on the cured layer. Examples of the light source include light emitting diodes (LEDs), mini LEDs, micro LEDs, etc. From the viewpoint of increasing the extraction efficiency of light emitted from the light source, it is preferable to arrange the light source in the cavity. In addition, the method for manufacturing a printed wiring board may include a step of electrically connecting the light source to the wiring and a step of sealing the light source.
[0152] For example, the method for manufacturing a printed wiring board may include a step of forming any layer, such as a conductor layer or an insulating layer, on the cured layer. In this case, the cured layer may be formed as an insulating layer by the above-mentioned method. For example, when the formation of an insulating layer and a conductor layer is repeated, the cured layer can function as an interlayer insulating layer.
[0153] [5. Manufactured printed wiring boards] Fig. 6 is a cross-sectional view showing an example of a printed wiring board manufactured by a manufacturing method according to an embodiment of the present invention. As shown in Fig. 6, the above-mentioned manufacturing method produces a printed wiring board 100 including a hardened layer 20 in which a cavity 60 is formed. The printed wiring board 100 usually includes a substrate 10 and a hardened layer 20 formed on the substrate 10.
[0154] The cured product contained in the cured layer 20 contains a white inorganic pigment (A-1), and therefore can have high light reflectance. Specifically, the reflectance of the cured product to light with a wavelength of 460 nm can be preferably 85% or more. The upper limit of the reflectance can be 100% or less, for example. Thus, the cured layer 20 can have high light reflectance. The reflectance of the cured product can be measured, for example, by polishing a cross section of the cured layer 20 and measuring the polished surface using a multichannel spectrometer (MCPD-7700, manufactured by Otsuka Electronics Co., Ltd.).
[0155] As described above, the cavity 60 is formed in the hardened layer 20 of the printed wiring board 100. The cavity 60 is a recess formed in the hardened layer 20, and may or may not penetrate the hardened layer 20. Since the above-mentioned manufacturing method can form the cavity 60 in the hardened layer 20 with excellent processability, the cavity 60 can have a wall surface 60W having a large gradient angle θ (0°≦θ≦90°). The gradient angle θ of the wall surface 60W of the cavity 60 is preferably 60° or more, and usually 90° or less. The gradient angle θ of the wall surface 60W of the cavity 60 represents the angle that the wall surface 60W of the cavity 60 forms with respect to the surface 20U of the hardened layer 20. The larger the gradient angle θ of the wall surface 60W of the cavity 60, the better the processability.
[0156] The gradient angle θ of the wall surface 60W of the cavity 60 can be measured by observing a cross section of the hardened layer 20 using a FIB-SEM composite device ("SMI3050SE" manufactured by SII Nanotechnology Co., Ltd.). Specifically, the hardened layer 20 is cut out using a FIB (focused ion beam) so that a cross section appears that is parallel to the thickness direction of the hardened layer 20 and passes through the center 60C of the bottom 60B of the cavity 60. The cross section is observed by a SEM (scanning electron microscope) to measure the gradient angle θ of the wall surface 60W.
[0157] The excellent workability of the cavity that can be achieved by the above-mentioned manufacturing method will be described below in comparison with the prior art. For example, consider a method of forming a cavity in a cured layer containing a white inorganic pigment using photolithography. In this method, light is reflected by the white inorganic pigment during the exposure process, and the light may penetrate into the area covered by the photomask. Therefore, the area that should not be exposed is exposed, making it difficult to form a cavity with the intended shape. In particular, it is difficult to make the slope angle of the wall of the cavity close to 90°.
[0158] Also, for example, a method of forming a cavity in a cured layer containing a white inorganic pigment using a laser beam is considered. In this method, a cavity is formed in the cured layer by the heat of the laser beam. However, in the cavity formed by the laser beam, a protrusion called a smear is generally formed. Therefore, in order to remove this smear, a desmearing process is usually performed to remove the smear using a chemical. However, in this method, the resin around the cavity is deteriorated by the heat of the laser beam, and the deteriorated resin may be further eroded by the chemical. This erosion may cause the cured layer and the substrate to peel off around the bottom of the cavity, forming a gap between the cured layer and the substrate.
[0159] In contrast, the sandblasting process employed in the above-mentioned manufacturing method avoids the effects of light reflection by white inorganic pigments, deterioration of the resin due to heat, and erosion by chemicals on the cavity. Therefore, the cavity can be selectively and accurately formed only in the portion corresponding to the opening of the mask. In addition, since the abrasive grains have difficulty penetrating the back side of the mask, it is easy to make the gradient angle of the cavity wall close to 90°. Therefore, the above-mentioned excellent workability can be achieved.
[0160] The cavity 60 of the cured layer 20 can have a small aspect ratio. The specific aspect ratio D / L of the cavity 60 is preferably 1.0 or less, more preferably 0.6 or less, and particularly preferably 0.3 or less. There is no particular limit to the lower limit, and it can be, for example, 0.01 or more, 0.05 or more, 0.1 or more, etc. According to the cavity 60 having an aspect ratio in such a range, the shape of the cavity 60 can be optimized, so that when the printed wiring board is applied to an LED display, it is possible to improve the luminous efficiency and achieve a long life. Here, the aspect ratio of the cavity 60 represents the ratio D / L obtained by dividing the depth D of the cavity 60 by the opening diameter L of the cavity 60. The opening diameter L of the cavity 60 represents the diameter of the opening of the cavity 60 on the surface 20U of the cured layer 20. This opening diameter L represents the diameter when the planar shape of the cavity 60 is circular, and represents the length of the long side when the cavity 60 is rectangular.
[0161] The opening diameter L of the cavity 60 is not particularly limited and can be set depending on the application of the cavity 60. From the viewpoint of effectively utilizing the advantage of excellent processability of the cavity 60, the opening diameter L is preferably 40 μm or more, more preferably 50 μm or more, particularly preferably 60 μm or more, and is preferably 500 μm or less, more preferably 300 μm or less, particularly preferably 200 μm or less.
[0162] The depth D of the cavity 60 is not particularly limited and can be set according to the application of the cavity 60. When the cavity 60 penetrates the hardened layer 20, the depth D of the cavity 60 is set to a value smaller than the thickness T of the hardened layer 20. 20 If the cavity 60 does not penetrate the hardened layer 20, the depth D of the cavity 60 may correspond to the thickness T of the hardened layer 20. 20 It could be something smaller.
[0163] Typically, the cavity 60 has a tapered shape in which the diameter of the bottom portion is smaller than the opening diameter L.
[0164] There is no particular limitation on the planar shape of the cavity 60, and it can be set depending on the application of the cavity 60. Examples of the planar shape of the cavity 60 include a circle, an ellipse, a square, a rectangle, and the like.
[0165] The cured layer 20 of the printed wiring board 100 usually has a thickness T 20 Therefore, the cured layer 20 of the printed wiring board 100 maintains the same thickness T 20 may have.
[0166] The cured layer 20 can be suitably used as a layer for light reflection (light reflection layer) for reflecting light from a light source (not shown) by utilizing its high light reflectance. Specifically, the cured layer 20 can be suitably used as a reflection sheet formed as the outermost layer of the printed wiring board 100. When used as a reflection sheet, the light source is usually installed in the cavity 60. The cured layer 20 can also be suitably used as a solder resist layer of the printed wiring board 100. The cured layer 20 may be used as a layer that serves both as a solder resist layer and a reflection sheet. In addition, since the cured layer 20 can usually have excellent insulation properties, it can be used as an insulation layer of the printed wiring board 100, and can also be used as an interlayer insulation layer. Among them, the cured layer 20 is preferably an interlayer insulation layer or a solder resist layer of the printed wiring board 100.
[0167] [6. Semiconductor Devices] The printed wiring board manufactured by the above-mentioned manufacturing method can be applied to, for example, a semiconductor device. Therefore, the printed wiring board manufactured by the above-mentioned manufacturing method can be applied to a manufacturing method of a semiconductor device. A semiconductor device including a printed wiring board can be manufactured by mounting a component (semiconductor chip) on a conductive portion of the printed wiring board. Examples of the semiconductor device include a semiconductor device mounted with a light-emitting diode (LED) that emits light with low power, such as a backlight for a liquid crystal display of a mobile terminal, a computer, a television, etc., and a light source for a lighting fixture. Among them, an LED display is preferable as the semiconductor device. EXAMPLES
[0168] The present invention will be specifically described below with reference to examples. The present invention is not limited to these examples. In the following, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Unless otherwise specified, the temperature and pressure conditions are room temperature (25°C) and atmospheric pressure (1 atm).
[0169] [Production Example 1. Production of resin sheet 1 including a layer of a thermosetting resin composition] Four parts of a liquid bisphenol A type epoxy resin (epoxy equivalent 180 g / eq., Mitsubishi Chemical Corporation's "Epikote 828EL"), four parts of a solid fluorine atom-containing epoxy resin (epoxy equivalent 245 g / eq., Mitsubishi Chemical Corporation's "YL7760"), and 20 parts of a phenoxy resin containing a biphenyl skeleton and a cyclohexane skeleton (Mitsubishi Chemical Corporation's "YL7200B35", MEK solution with a solid content of 35 mass %) were heated and dissolved in 8 parts of MEK with stirring. To this were mixed 10 parts of titanium oxide (average particle size 0.26 μm, Sakai Chemical Industry Co., Ltd. "PX3788", with phenylsilane treatment), 10 parts of spherical silica (average particle size 0.5 μm, Admatechs Co., Ltd. "SO-C2", with aminosilane treatment), 4 parts of bisphenol AF (a solution of Central Glass Co., Ltd. "BiS-AF" adjusted with MEK to a non-volatile content of 50%), and 0.2 parts of a curing accelerator (Hokko Chemical Industry Co., Ltd. phosphorus-based catalyst "TBP-DA"), and the mixture was uniformly dispersed using a high-speed rotating mixer to prepare a varnish-like resin composition.
[0170] A PET film with a release layer ("PET501010" manufactured by Lintec Corporation, thickness 38 μm) was prepared as a support. The varnish-like resin composition was uniformly applied onto the release layer of this support so that the thickness of the resin composition layer after drying was 20 μm. The resin composition was then heated at 80° C. for 4 minutes to obtain a resin sheet 1 including a resin composition layer having a thickness of 20 μm.
[0171] [Production Example 2. Production of resin sheet 2 including a layer of a thermosetting resin composition] The amount of the varnish-like resin composition applied was changed so that the thickness of the resin composition layer after drying was 100 μm. A resin sheet 2 including a resin composition layer having a thickness of 100 μm was produced in the same manner as in Production Example 1 except for the above.
[0172] [Production Example 3. Production of resin sheet 3 including a layer of a thermosetting resin composition] Bisphenol AF (a solution of "BiS-AF" manufactured by Central Glass Co., Ltd. adjusted with MEK to a non-volatile content of 50%) (4 parts) was not used. In addition, the amount of the varnish-like resin composition applied was changed so that the thickness of the resin composition layer after drying was 50 μm. A resin sheet 3 including a resin composition layer having a thickness of 50 μm was produced by the same method as in Production Example 1 except for the above.
[0173] [Production Example 4. Production of resin sheet 4 including a layer of a thermosetting resin composition] The amount of titanium oxide (average particle size 0.26 μm, Sakai Chemical Industry Co., Ltd. "PX3788", phenylsilane treatment) was changed from 10 parts to 20 parts. In addition, spherical silica (average particle size 0.5 μm, Admatechs Co., Ltd. "SO-C2", aminosilane treatment) was not used. Furthermore, the amount of varnish-like resin composition applied was changed so that the thickness of the resin composition layer after drying was 50 μm. A resin sheet 4 including a resin composition layer having a thickness of 50 μm was produced by the same method as in Production Example 1 except for the above.
[0174] [Production Example 5. Production of resin sheet 5 including a layer of a thermosetting resin composition] Spherical silica (average particle size 0.5 μm, Admatechs' "SO-C2", aminosilane-treated) was not used. In addition, the amount of the varnish-like resin composition applied was changed so that the thickness of the resin composition layer after drying was 50 μm. A resin sheet 5 including a resin composition layer having a thickness of 50 μm was produced by the same method as in Production Example 1, except for the above.
[0175] [Production Example 6. Production of resin sheet 6 including a layer of a photosensitive resin composition] Three parts of a biphenyl type epoxy resin (epoxy equivalent: about 272 g / eq., Nippon Kayaku Co., Ltd. "NC3000H"), two parts of a tetrakishydroxyphenylethane type epoxy resin (epoxy equivalent: about 200 g / eq., Mitsubishi Chemical Co., Ltd. "1031S"), ten parts of a bisphenol A type epoxy acrylate (acid value: 99 mgKOH / g, solids concentration: about 70%, Nippon Kayaku Co., Ltd. "ZAR-2000"), and one part of dipentaerythritol hexaacrylate (acrylic equivalent: about 96 g / eq., Nippon Kayaku Co., Ltd. "DPHA") were dissolved in six parts of MEK and ten parts of ethyl diglycol acetate under heating with stirring. To this was added 4 parts of titanium oxide (average particle size 0.26 μm, Sakai Chemical Industry Co., Ltd. "PX3788", treated with phenylsilane), 4 parts of spherical silica (average particle size 0.5 μm, Admatechs Co., Ltd. "SO-C2", treated with aminosilane), and 0.04 parts of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (BASF "Irgacure819"), which was then uniformly dispersed using a high-speed rotating mixer to prepare a varnish-like photosensitive resin composition.
[0176] A resin sheet 6 including a resin composition layer having a thickness of 20 μm was obtained by the same method as in Production Example 1, except that the photosensitive resin composition prepared in Production Example 6 was used instead of the resin composition prepared in Production Example 1.
[0177] [Example 1] (1) Lamination of resin sheet: An inner layer circuit board (manufactured by Panasonic, "R-1766") was prepared, in which the copper surface was roughened (amount of copper etched: 0.5 μm, arithmetic mean roughness after roughening treatment (Ra): 310 nm, arithmetic ten-point mean roughness after roughening treatment (Rz): 3920 nm) using a microetching agent (manufactured by Mec, "CZ8201"). The resin sheet 1 manufactured in Manufacturing Example 1 was laminated on both sides of this inner layer circuit board using a batch-type vacuum pressure laminator (manufactured by Meiki, "MVLP-500"). The lamination was performed so that the resin composition layer of the inner layer circuit board and the resin sheet 1 were in contact with each other. The lamination was also performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing for 30 seconds at 100°C and a pressure of 0.74 MPa.
[0178] (2) Curing of resin composition layer: The support was peeled off from the laminated resin sheet 1, and the resin composition layer was thermally cured under curing conditions of 180° C. and 30 minutes to form a cured layer.
[0179] (3) Mask placement: A dry film containing a polyethylene terephthalate film as a protective layer (Nikko Materials' "ALPHO 20A263", 50 μm thick) was attached to the surface of the cured layer formed on the inner layer circuit board. The dry film was attached using a batch-type vacuum pressure laminator (Meiki Seisakusho's "MVLP-500"), which was depressurized for 30 seconds to a pressure of 13 hPa or less, and then pressurized for 20 seconds at a pressure of 0.1 MPa and a temperature of 70°C.
[0180] Then, a glass mask having a cavity pattern was placed on a polyethylene terephthalate film as a protective layer for the dry film. Then, a UV lamp was used to irradiate the film with an irradiation intensity of 150 mJ / cm. 2The dry film was irradiated with ultraviolet light through a glass mask. After the ultraviolet light irradiation, the glass mask and the protective layer of the dry film were removed, and a 1% aqueous sodium carbonate solution at 30°C was sprayed onto the dry film at a spray pressure of 0.15 MPa for 30 seconds. After that, the dry film was washed with water, and a patterned dry film having a square opening of 100 μm on each side was placed on the cured layer as a mask.
[0181] (4)Sandblasting: Alumina particles (average particle size 4.0 μm, modified Mohs hardness 12, "DAW-03" manufactured by Denka) were used as abrasive grains, and the hardened layer was subjected to dry blasting at a processing pressure of 0.2 MPa. In this dry blasting, abrasive grains were sprayed from the nozzle of the processing device and collided with the hardened layer through the openings in the patterned dry film. At this time, the abrasive grains did not collide with the hardened layer in areas other than the openings in the patterned dry film, as they were blocked by the patterned dry film. Multiple cavities with the same planar shape as the openings in the patterned dry film were formed in the hardened layer.
[0182] (5) Peeling off the dry film: A 3% sodium hydroxide solution at 50°C was sprayed onto the patterned dry film at a spray pressure of 0.2 MPa, and the dry film was peeled off. After that, it was washed with water and dried at 150°C for 30 minutes to obtain an evaluation wiring board having an inner layer circuit board and a hardened layer with a cavity formed therein.
[0183] [Example 2] An evaluation wiring board having an inner layer circuit board and a hardened layer having a cavity formed therein was obtained in the same manner as in Example 1, except that resin sheet 3 produced in Production Example 3 was used instead of resin sheet 1.
[0184] [Example 3] An evaluation wiring board having an inner layer circuit board and a cured layer having a cavity formed therein was obtained in the same manner as in Example 1, except that resin sheet 4 produced in Production Example 4 was used instead of resin sheet 1.
[0185] [Example 4] An evaluation wiring board having an inner layer circuit board and a cured layer having a cavity formed therein was obtained in the same manner as in Example 1, except that resin sheet 5 produced in Production Example 5 was used instead of resin sheet 1.
[0186] [Example 5] An evaluation wiring board having an inner layer circuit board and a cured layer having a cavity formed therein was obtained in the same manner as in Example 1, except that resin sheet 2 produced in Production Example 2 was used instead of resin sheet 1.
[0187] [Example 6] Except for carrying out wet blasting instead of dry blasting, an evaluation wiring board including an inner layer circuit board and a hardened layer having a cavity formed therein was obtained by the same method as in Example 1. This wet blasting was carried out by the same method as in Example 1, except for using a slurry containing alumina particles (alumina particles: average particle size 4.0 μm, modified Mohs hardness 12, Denka "DAW-03"; abrasive concentration 20%) instead of alumina particles (average particle size 4.0 μm, modified Mohs hardness 12, Denka "DAW-03");
[0188] [Comparative Example 1] The same inner layer circuit board as in Example 1 was prepared. The resin sheet 6 produced in Production Example 6 was laminated on both sides of this inner layer circuit board using a batch type vacuum pressure laminator ("MVLP-500" manufactured by Meiki Co., Ltd.). The lamination was performed under the same conditions as in Example 1 so that the inner layer circuit board and the resin composition layer of the resin sheet 6 were in contact with each other.
[0189] A glass mask having a cavity pattern was placed on the support of the resin sheet 6 laminated to the inner layer circuit board. Then, irradiation intensity was 100 mJ / cm 2The resin composition layer was irradiated with ultraviolet light through a glass mask to photocure the exposed portion of the resin composition layer. After the ultraviolet light irradiation, the glass mask and the support of the resin sheet 6 were removed, and the entire surface of the resin composition layer was sprayed with a 1% by mass aqueous solution of sodium carbonate at 30° C. as a developing solution at a spray pressure of 0.2 MPa for 2 minutes to perform development. By this development, the resin composition in the non-exposed portion was removed, and multiple cavities were formed in the resin composition layer.
[0190] After development, the resin composition layer was exposed to 1 J / cm 2 The resin composition layer was then sufficiently cured by irradiating the inner layer circuit board with ultraviolet light for 90 minutes at 190°C. This resulted in a wiring board for evaluation that had an inner layer circuit board and a cured layer as the cured resin composition layer. The cured layer had a cavity formed in the same planar shape as the light-shielding portion of the glass mask (portion that blocks ultraviolet light).
[0191] [Comparative Example 2] Resin sheet 6 produced in Production Example 6 was used instead of resin sheet 1. In addition, in the step of curing the resin composition layer of resin sheet 6 laminated to the inner layer circuit board to form a cured layer, the resin composition layer was cured by photocuring. In this photocuring, 100 mJ / cm was applied to the resin composition layer. 2 of ultraviolet light; 1 J / cm 2 and a heat treatment was performed at 190° C. for 90 minutes. Except for the above, a wiring board for evaluation including an inner layer circuit board and a cured layer having a cavity formed therein was obtained by the same method as in Example 1.
[0192] [Comparative Example 3] Resin sheets 1 were laminated on both sides of the inner layer circuit board in the same manner as in Example 1, and the resin composition layer was thermally cured to form a cured layer. Thereafter, the cured layer was irradiated with CO2 laser light under the conditions of a mask diameter of 1 mm, a pulse width of 16 μs, an energy of 0.2 mJ / shot, a shot number of 10, and a burst mode (10 kHz) to form a plurality of cavities having square openings with sides of 100 μm.
[0193] Thereafter, a desmearing process was performed to remove the smears in the cavities. In this desmearing process, the cured layer was immersed in a swelling liquid, Swelling Dip Securigand P, containing diethylene glycol monobutyl ether, manufactured by Atotech Japan, for 5 minutes at 60°C. Next, the cured layer was immersed in Concentrate Compact P (aqueous solution of KMnO4: 60g / L, NaOH: 40g / L) manufactured by Atotech Japan, for 15 minutes at 80°C as a roughening liquid. Next, the cured layer was immersed in Reduction Showreusin Securigand P, manufactured by Atotech Japan, for 5 minutes at 40°C as a neutralizing liquid. After that, it was dried at 80°C for 30 minutes to obtain an evaluation wiring board having an inner layer circuit board and a cured layer in which a cavity was formed.
[0194] [Evaluation of cavity workability] Ten cavities were arbitrarily selected from the same evaluation wiring board. The selected cavities were subjected to cross-sectional observation using a FIB-SEM composite device ("SMI3050SE" manufactured by SII Nano Technology Co., Ltd.). In detail, the hardened layer was cut out using a FIB (focused ion beam) so that a cross section parallel to the thickness direction of the hardened layer and passing through the center of the bottom of the cavity appeared. This cross section was observed using a SEM (scanning electron microscope) to obtain the average of the gradient angles of the wall surfaces of the 10 cavities. If the average gradient angle was 60° or more, it was judged to be "good". If the average gradient angle was less than 60°, it was judged to be "poor". In addition, with regard to Comparative Example 3, a gap formed by the hardened layer peeling off from the copper foil layer on the surface of the inner layer circuit board was observed, continuing from the edge of the bottom of the cavity, and therefore it was judged to be "poor".
[0195] [Measurement of cavity aspect ratio] Ten cavities were randomly selected from the same evaluation wiring board. For each of the selected cavities, the depth of the cavity was divided by the opening dimension of the cavity to obtain the aspect ratio. In the above-mentioned examples and comparative examples, the cavity had a rectangular opening in plan view, so the length of the long side of the rectangle was used as the opening dimension. The average of the aspect ratios of the 10 points was calculated and shown in the table below.
[0196] [Measurement of reflectance of cured resin composition] The wiring board for evaluation was cut into a width of 50 mm and a length of 50 mm, and the cross section was polished. The reflectance of the cured layer at a wavelength of 460 nm was measured on the cross section using a multichannel spectrometer ("MCPD-7700" manufactured by Otsuka Electronics Co., Ltd.). If the reflectance was 85% or more, it was judged as "good", and if it was less than 85%, it was judged as "poor".
[0197] [result] The results of the Examples and Comparative Examples are shown in the following table. In the table, the abbreviations have the following meanings. Proportion of white inorganic pigment: Proportion of white inorganic pigment relative to 100 mass% of non-volatile components of the resin composition. Proportion of inorganic filler: Proportion of inorganic filler relative to 100 mass% of non-volatile components of the resin composition. DB: Dry blasting. WB: Wet blasting. WD: Wet desmear treatment.
[0198] [Table 1] [Explanation of symbols]
[0199] 10 Substrate 20 hardening layer 20U Hardened layer surface 30 Dry Film 40 Photomask 50 Pattern Dry Film 51 Aperture 60 Cavity 60B Bottom of cavity 60C Center of bottom of cavity 60W cavity wall 100 Printed wiring board
Claims
1. A step of preparing a cured layer formed of a cured product of a thermosetting resin composition containing an inorganic filler including a white inorganic pigment; and performing a sandblasting process on the hardened layer to form a cavity. The method for producing a printed wiring board, wherein the resin composition contains 10 mass % or more and 75 mass % or less of a thermoplastic resin (C) when a resin component in the resin composition is taken as 100 mass %.
2. The method for producing a printed wiring board according to claim 1 , wherein the cured product has a reflectance of 85% or more with respect to light having a wavelength of 460 nm.
3. The aspect ratio of the cavity is 1.0 or less; 3. The method for manufacturing a printed wiring board according to claim 1, wherein a gradient angle of a wall surface of the cavity is 60 degrees or more.
4. The method for producing a printed wiring board according to any one of claims 1 to 3, wherein the cured layer has a thickness of 5 µm or more and 150 µm or less.
5. The amount of the inorganic filler is 20% by mass or more and 70% by mass or less with respect to 100% by mass of the non-volatile components of the resin composition, The method for producing a printed wiring board according to any one of claims 1 to 4, wherein the amount of the white inorganic pigment is 10% by mass or more and 60% by mass or less with respect to 100% by mass of non-volatile components of the resin composition.
6. The method for producing a printed wiring board according to any one of claims 1 to 5, wherein the resin composition contains an epoxy resin.
7. The method for producing a printed wiring board according to any one of claims 1 to 6, wherein the step of preparing the cured layer includes the steps of preparing a layer of the resin composition and thermally curing the layer of the resin composition.
8. The method for manufacturing a printed wiring board according to any one of claims 1 to 7, wherein the step of forming the cavity includes the steps of: placing a mask having an opening on the hardened layer; and spraying abrasive grains through the opening of the mask onto the hardened layer.
9. The method for producing a printed wiring board according to claim 8, wherein the average particle size of the abrasive grains is 0.5 μm or more and 50 μm or less.
10. The method for producing a printed wiring board according to claim 8 or 9, wherein the abrasive grains have a modified Mohs hardness of 5 or more.
11. The method for producing a printed wiring board according to any one of claims 1 to 10, wherein the hardened layer is an interlayer insulating layer or a solder resist layer of the printed wiring board.
12. The method for producing a printed wiring board according to any one of claims 1 to 11, further comprising a step of arranging a light source on the cured layer.
Citation Information
Patent Citations
Purification of 27-desamidosecretin
JP1985078595A
Method of manufacturing wiring board
JP2008041932A
Thermosetting resin composition for light reflector, light reflector and light-emitting device
JP2015152643A
Material for forming light reflector, light reflector, and light-emitting device
JP2020067603A
Manufacturing method of print circuit board
JP2020140990A